Evaluating the Ineffectiveness of Chest Physiotherapy in Airway Clearance for Pneumonia Patients in the Hospital - Budi, Fandi Ahmad Kurniawan Setia (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Pneumonia is a respiratory disorder that commonly affects children. It is often characterized by weakened vesicular breath sounds, along with fine and coarse crackles, which can lead to ineffective airway clearance. Chest physiotherapy is one of the treatments administered to pneumonia patients with impaired oxygenation. This study aims to describe the application of chest physiotherapy in managing ineffective airway clearance in pneumonia patients in the Aster Room of RSD dr. Soebandi Jember. This research employs a case study approach conducted over three days. Data collection methods included interviews, measurements, and observations. The evaluation results showed that the patient experienced a reduction in secretion production, as evidenced by decreased rhonchi sounds and reduced cough intensity. Chest physiotherapy has been proven effective in clearing sputum from the airways and reducing cough intensity in pneumonia patients.